Impact of Goods and Services Tax on the Malaysian economy / Juliana Mohamed Abdul Kadir - Juliana , Mohamed Abdul Kadir (2017)
This study examines the impact of the goods and services tax (GST) on the Malaysian economy from three major perspectives. First, it investigates the consequent changes in sectoral responses, including output, sales, and prices for 15 main sectors. Second, the study presents the results of GST impact on seven macroeconomic variables, namely, consumption, investment, government revenue, government expenditure, export, import, and gross domestic product. Third, the results of household welfare are discussed. A computable general equilibrium model is utilized to simulate GST impact on the Malaysian economy, and a simple comparative static model is performed. Three simulations are carried out to examine the impact of GST when it is imposed at 4 percent (Simulation 1), 6 percent (Simulation 2), and 8 percent (Simulation 3). The analysis proceeds with the findings based on all simulations taken. The results prove that the higher the GST rate introduced, the higher the impact is on each sector. The sectors most affected by GST are communication and ICT and the electricity and gas sectors. By contrast, agriculture, forestry, and logging and the petroleum and natural gas sectors are the least affected. Most of the examined factors are adversely affected by GST. Consumption and investment receive the largest negative effect, whereas government revenue and expenditure show the largest positive effect. The study likewise finds that welfare loss may be minimized by lowering GST rate, and higher-income groups may be affected more than lower-income groups. Therefore, policymakers should promote the service sector as an engine for other sectors to generate economic growth, given that it will produce a more stable source of revenue in the long run. Importantly, GST is an effective method to broaden the country’s revenue base and improve the efficiency of the tax system. This outcome is similar to the primary aim of GST to reduce the fiscal deficit of the country. With budget surpluses, the government could afford to give away sufficient tax rate offset to cushion the effects of GST. In a nutshell, GST is a useful complement to the economy when it is charged at the minimum rate. A 6 percent rate is a reasonable initial rate. However, should the rate fluctuate, low-income earners may suffer a setback owing to their small consumption power. Therefore, GST should be stabilized at a lower rate for a period of at least five years.